FRI0070 Ultrasound doppler activity correlates with systemic autoimmunity and swollen joints in a healthy population at risk for rheumatoid arthritis. (23rd January 2014) - Brulhart, L.; Ciubotariu, E.; Nissen, M. J.; Gascon, D.; Bas, S.; Gabay, C.; Finckh, A.
Abstract : Background: Diagnosing rheumatoid arthritis (RA) early and identifying pre-clinical RA has become a high-stakes undertaking. In RA patients, musculoskeletal ultrasound (US) is more sensitive than clinical assessment for synovitis detection. Whether US is associated with joint involvement in healthy individuals at increased risk for RA is unknown. Objectives: To assess the value of US to detect specific phases leading to the development of RA in a healthy population at increased risk of RA. Methods: This study is nested within an ongoing prospective cohort study of healthy first-degree relatives of RA patients (FDRs), who had no established rheumatic disease at inclusion. Data collection included health questionnaires, physical examination and blood tests, including inflammatory markers, HLA-DR genotyping, rheumatoid factor (RF) and anti-cyclic citrullinated peptide antibodies (anti-CCP2) levels by ELISA. A standardized US examination was performed according to the OMERACT criteria: synovitis was scored in B-mode and Doppler by a semi-quantitative scale ranging from 0 to 3 on MCPs and PIPs 2 to 5, wrists, olecranon fossa and knees. A composite endpoint of either presence of auto-antibodies (RF-IgM, RF-IgA or anti-CCP2) or at least one swollen joint on physical examination was chosen (group 1) . To test if US was independently associated with the primary end point, we used logistic regression, adjusting for potential confounders such as age, sex, body mass index, Caucasian race and smoking. Results: One hundred consecutive healthy FDRs were included in this analysis. Baseline characteristics were similar between the two groups except for swollen joints and RF by definition (table 1 ). Doppler activity was detected significantly more often in group 1 (60%) than in the control group (34%) (p=0.05, adjusted OR: 3.02 (95%CI: 0.82 – 11.1). The mean Doppler score was also significantly higher in group 1: 1.46 compared to 0.62 (p=0.02, adjusted OR: 1.64 (95%CI: 1.01 – 2.66)). However, neither the presence of synovitis grade 2 or 3 on B-mode (47% versus 42%, p=0.76) nor the median B-mode score (6 (IQR: 4 – 9) versus 6 (IQR: 4 – 10), p=0.75) allowed to discriminate the two groups. Conclusions: Doppler signal on US was associated with the presence of auto-antibodies or clinical signs of synovitis, thus identifying early signs of arthritis in a population at risk to develop RA. Disclosure of Interest: None Declared